PENGARUH KOMPETENSI, KOMITMEN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT. BANK RAKYAT INDONESIA (PERSERO) KANTOR WILAYAH PEKANBARU - Shaputra, Angga Rahyu; Hendriani, Susi (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to determine the effect of Competence, Organizational Commitment and Career Development on Employee Performance Bank Rakyat Indonesia Pekanbaru Regional Office. The method of analysis used in this study is descriptive statistical analysis method and inferential statistics through Multiple Regression. The method of research using survey methods, of the number of population of 1101 employees of Bank Rakyat Indonesia Regional Office Pekanbaru taken a sample of 294 respondents with a stratified random sampling technique. Before testing the hypothesis, test the validity and reliability of the primary data questionnaire using SPSS version 17.0. Regression equations were then tested with analysis of classical assumption of normality test, Multicollinearity Test, Test and Test Heteroskidastity autocorrelation. Analysis of the influence of the independent variables with the dependent variable analysis performed with the t test, F test, the coefficient of determinant (R2) and correlation coefficient (R). The results showed a partial factor of career development does not affect the performance of the employee, but simultantly, competency, commitment and career development have an influence on the performance of the employees of Bank Rakyat Indonesia Pekanbaru Regional OfficeKeywords: Competence, Commitment, Career Development, Performance